Professional Training: the problem of complex learning at the University. The Investigation of a case in the Odontology area (Praxis Educativa, 2012)
This paper presents the advances of the Project of investigation “Training spaces for complex learning of the professional practice at the degree careers of the Buenos Aires University (BAU)”. This work is focused on the problem of training in the profession and the place of the complex learning at the university through the study of the subjects of Odontology at the BAU. In this sense, we analyse the different instances in which this training becomes possible, to see the different teaching method expressed in them and, at the same time, the ways in which the relationship theory and practice occur. In this way, we study, including the socio historical approach, the project that supports the subject, its forms of organization, the strategies used in theoretical classes an the peculiarities of teaching in the Clinics.
Keywords: university education; profession; complex knowledge; complex learning; clinics; logics